Quality changes of fluvial sediments impacted by urban effluents in Ushuaia, Tierra del Fuego, southernmost Patagonia - Diodato, Soledad Lorena; Gonzalez Garraza, Gabriela Carolina; Mansilla, Paula Romina; Moretto, Alicia Susana; Escobar, Julio Martin; Méndez López, Melissa; Gómez Armesto, Antía; Marcovecchio, Jorge Eduardo; Nóvoa Muñoz, Juan Carlos (Environmental Earth Sciences)
Bottom sediments play a fundamental role in the eutrophication process because they are one of the most active compartments in the biogeochemical cycle of nutrients. In Ushuaia city, Tierra del Fuego, Argentina, sewage effluents have been discharged into natural watercourses without treatment for many years. Organic matter has been introduced until 2016 when improvements in sewage infrastructure were done. The quality of surface sediments from three watercourses with different degree of impact has been studied taking into account contrasting hydrological periods. pH, organic carbon (OC), total nitrogen (TN) and soluble reactive phosphorus (SRP) were measured in austral autumn and spring between 2013 and 2018 in three sections of each watershed. Nutrient content in sediments of upstream sites derives from the contribution of Nothofagus spp. forests through litter-fall. Middle and downstream sites were the most affected by wastewater discharges evidencing that fluvial sediments act as a receptor of the allochthonous organic loads. Particularly, sediments of Buena Esperanza Stream had the lowest mean pH (5.44) and the highest mean concentrations of OC (42.95 mg g−1), TN (2.53 mg g−1) and SRP (0.067 mg g−1), along with the lowest mean annual flow and the largest urbanized area. No differences between hydrological periods were found, although TN and SRP contents were higher in autumn than in the snowmelt season. Minimal differences in nutrients between before and after infrastructure improvement were found. Even when external contributions have been decreased, more time will be necessary to reduce eutrophic conditions of fluvial sediments in southernmost Patagonia. Fil: Diodato, Soledad Lorena. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Gonzalez Garraza, Gabriela Carolina. Consejo ...